Answer:
B) → x-intercept = (6, 0) and y-intercept = (0, -9.)
First, we'll work with y, where we'll substitute x by 0:
3(0) - 2y = 18
0 - 2y = 18
-2y = 18 + 0
-2y = 18
y = 18 / -2
y = -9 → y-intercept = 0, -9 ←
↑ Many people wonder where the "0" comes from, and it's just the place where the x-intercept value would be placed in a system of equations.
Second, we'll work with x, following the same method as before, this time, substituting y by 0:
3x - 2(0) = 18
3x - 0 = 18
3x = 18 + 0
3x = 18
x = 18 / 3
x = 6 → x-intercept = 6, 0 ←
↑ Same here. The "0" is just the place where the y-intercept value would be, if we were working with a system of equations.
Hope it helped
BioTeacher101